Employee perception on practice of knowledge management in water industry : case study of SAJ Holdings Sdn. Bhd. - Mustapha, Ishamuddin (2009)
This research was carried out to study the employee perception towards the practice of knowledge management in one of the water utility provider in Malaysia, which is SAJ Holdings Sdn Bhd. The selected company is currently in the stage of implementing the knowledge management in the organization and therefore the research will be very useful and important to the organization. The research covers all important aspect as to support the effort to inculcate culture of knowledge management. The main objective of the study is to analyzed the employee’s perception and level of understanding towards the practice of knowledge management. This study also sought to understand the support factors for employees to contribute in knowledge management practice, to analyzed the employee perception on KM facilities as well as to understand the relations between level of employee awareness and understanding on KM and the pre-identified variables. The respondents are of employee in non-managerial positions and the data has been collected by using questionnaire distributed throughout the operational coverage of the selected organization. Descriptive and inferential analysis has been conducted to all data collected and all research findings are really interesting and beyond the expectation. All research questions have managed to be answered successfully and all hypotheses that being set earlier had managed to be solved with appropriate justification. The research results obtained is very useful to the organization as well as for the employee. Several recommendations have been suggested to the organization base on the research findings. The research findings can also being a guidance and reference to other organization embarking knowledge management. The research conducted also very useful to the water industry in Malaysia where indirectly it can help to enhance the industry human capital competencies. Moreover, others organization can concentrate to the research findings as one of the lesson learn in practicing knowledge management in their organization